2021
DOI: 10.3390/ijms222111538
|View full text |Cite
|
Sign up to set email alerts
|

DUSP9, a Dual-Specificity Phosphatase with a Key Role in Cell Biology and Human Diseases

Abstract: Mitogen-activated protein kinases (MAPKs) are essential for proper cell functioning as they regulate many molecular effectors. Careful regulation of MAPKs is therefore required to avoid MAPK pathway dysfunctions and pathologies. The mammalian genome encodes about 200 phosphatases, many of which dephosphorylate the MAPKs and bring them back to an inactive state. In this review, we focus on the normal and pathological functions of dual-specificity phosphatase 9 (DUSP9)/MAP kinase phosphatases-4 (MKP-4). This cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 87 publications
0
15
0
2
Order By: Relevance
“…Furthermore, understanding the mechanisms behind sustained MAPK signaling in insulin resistance is important and adds relevance to our observation of the down-regulated phosphorylation levels of the ERK phosphatase, DUSP9. Increased levels of this phosphatase have been shown to protect against insulin resistance [65], [66], [82]. The potential regulatory role of the significantly regulated C-terminal phosphorylation sites of DUSP9 identified in this study is unknown.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, understanding the mechanisms behind sustained MAPK signaling in insulin resistance is important and adds relevance to our observation of the down-regulated phosphorylation levels of the ERK phosphatase, DUSP9. Increased levels of this phosphatase have been shown to protect against insulin resistance [65], [66], [82]. The potential regulatory role of the significantly regulated C-terminal phosphorylation sites of DUSP9 identified in this study is unknown.…”
Section: Discussionmentioning
confidence: 92%
“…Noteworthy, only insulin-resistant cells showed upregulated phosphorylation levels of DUSP9 Ser368 and Thr384 upon insulin stimulation (>1.5-fold at 3 nM and >2-fold at 100 nM, p<0.05) (Figure S4.C). DUSP9 dephosphorylates MAPKs, including ERK1/2 [65], and several studies have shown its involvement in insulin resistance [66]- [68]. Thus, it was speculated whether the lowered phosphorylation levels of DUSP9 at Ser368 and Thr384 under unstimulated insulin-resistant conditions, potentially impact the activity or stability of the protein, leading to sustained ERK phosphorylation and signaling.…”
Section: Phosphoproteome Analysis Uncovers Sustained Erk Signaling An...mentioning
confidence: 99%
“…The PD-1/PD-L1 pathway is currently one of the main targets of immunologic drugs for the treatment of lung cancer, and some studies have shown that IPF patients with concurrent enlarged lymph nodes have higher PD-1 expression and CD4/CD8 ratios, whereas pembrolizumab shows antifibrotic effects in the bleomycin model in mice [33,34]. In addition, the dualspecificity protein phosphatase protein family (DUSP10/ MKP-5, DUSP9/ MKP-4) shows antagonistic effects in cancer and fibrosis [35,36]. This reminds us that for this easily overlooked population, they urgently need to find a common target of anti-cancer and anti-fibrosis, and also need a consensus statement of unified standard methods.…”
Section: Discussionmentioning
confidence: 99%
“…DUSP9 принадлежит к семейству протеинфосфатаз, негативно регулирующих ERK1/2, p38 и JNK MAP-киназы, дефосфорилируя их как по тирозиновым, так и по серин/треониновым остаткам. На 2021 г. в человеческом геноме выявлена 61 протеинфосфатаза такого типа [3].…”
Section: Introductionunclassified
“…Мы также выя-вили связь транскрипционной активности DUSP9 c определенными модификациями гистона H3 в локусе гена, что свидетельствует о возможном вовлечении процесса модификации гистонов в регулирование активности гена DUSP9 [14]. Кроме эпигенетических, активность DUSP9 в опухолях человека может регулироваться на транскрипционном и пост-транскрипционном уровнях [3].…”
Section: Introductionunclassified